Peran Moderasi Kantor Akuntan Publik Big 4 Pada Pengaruh Financial distress Terhadap Earning Management - Santoso, Rizhika Velajani; Suhadak, Suhadak (E-Jurnal Akuntansi; Vol 32 No 9 (2022)DO - 10.24843/EJA.2022.v32.i09.p05, 2022)
This study examines the effect of financial distress on earnings management by being moderated by KAP BIG 4, leverage and CFO with the aim of being able to minimize earnings management behavior to solve agency problems. This research was conducted on agricultural and mining sector companies. The final sample was 105, using purposive sampling method and using Moderated Regression Analysis (MRA) analysis technique. The results of the analysis show that financial distress has a positive effect on earnings management in agricultural and mining sector companies. Financial distress conditions encourage earnings management behavior. KAP BIG 4 has not been able to moderate the effect of financial distress on earnings management. Suggestions for further research can be to research more broadly in the manufacturing sector and add variables such as tax avoidance or ROE and DER. Keywords: Financial Distress; Earnings Management; Agency Theory; KAP BIG 4